Edukasi manajemen teknologi produksi untuk menunjang kehalalan produk bagi usaha kecil menengah (Productiom technology management education to support halal products for small scale enterprises) - Khathir, Rita; Yunita, Yunita; Rahmawati, Marai (Buletin Pengabdian, 2023)
This community service aimed to educate the small and medium enterprises (SMEs) about management of production technologies in obtaining halal certification. The partners of this program were UKM Meugah Pliek and UKM Wina Mandiri as pliek-u and asam sunti processors in Aceh Besar Regency. The production steps of the products that need technology are drying and pressing process. This program had been conducted through survey, preparation, and education. Results of this program were 2 hours training on production technology management to support halal products, 1 unit Hohenheim Aceh solar tunnel dryer, 1 unit hydraulic press, 4 units digital balance at capacity of 40kg and 1000pc of thin wall plastic containers. The technologies adapted were believed to support the production process in order to warrant the halal products. The results of the program were also published on online media to transfer knowledge and motivation to wider community. The participants showed high enthusiasm to the program as it can increase not only their knowledge but also provide technologies and tools to be used in supporting halal production.